2022
DOI: 10.1038/s41598-022-09470-9
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory neurons in paraventricular hypothalamus contributed to the mechanism underlying acupuncture regulating the swallowing function

Abstract: Paraventricular hypothalamus (PVH) is demonstrated to regulate stress, feeding behaviors, and other related homeostatic processes. However, no direct evidence has been investigated for the role of PVH in swallowing function. Acupuncture therapy at Lianquan (CV23) acupoint has been reported to improve the swallowing function in clinical trials, but its underlying mechanism still needs to be uncovered. Thus, we aimed to explore whether PVH involved the acupuncture mediated regulating swallowing function. Chemoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…These results suggested that dysphagia could be induced by photothrombotic ischemia in the M1, and thus proved the successful establishment of the PSD mouse model. These observations were consistent with our previous results 43 45 , which indicated that focal ischemia in the M1 can induce impaired EMG responses in the mylohyoid and decreased water consumption in mice. Next, to determine whether EA-CV23 attenuated the swallowing difficulty in PSD model mice, EMG recordings in the mylohyoid and the water consumption test were performed 24 h following EA-CV23.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These results suggested that dysphagia could be induced by photothrombotic ischemia in the M1, and thus proved the successful establishment of the PSD mouse model. These observations were consistent with our previous results 43 45 , which indicated that focal ischemia in the M1 can induce impaired EMG responses in the mylohyoid and decreased water consumption in mice. Next, to determine whether EA-CV23 attenuated the swallowing difficulty in PSD model mice, EMG recordings in the mylohyoid and the water consumption test were performed 24 h following EA-CV23.…”
Section: Resultssupporting
confidence: 94%
“…The mice were placed in an anesthesia induction box containing 4% isoflurane in an oxygen/air mixture until anesthetized, and then transferred to an anesthetic mask to maintain anesthesia with 2% isoflurane provided by an animal anesthesia machine (R500, RWD, China). Then the tail was soaked in warm water at 38 ± 2°C to expand the tail vein, and the tail vein was injected with 15 mg/ml RB solution (diluted with 0.9% saline, Sigma, USA) as previously described 45 , 79 . The coordinates of the M1 (AP: −0.12 mm, ML: −1.03 mm) and PFC (AP: −0.3 mm, ML: −1.75 mm) were selected based on the PRV labeling regions and the Paxinos and Franklin Mouse Brain Atlas (second edition).…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations have reported that neural activity in the primary motor cortex (M1) was enhanced by EA‐CV23 in PSD mice. 8 , 9 , 10 , 11 When acupuncture is delivered to acupoints, the cortex is activated. 12 , 13 Nevertheless, the pathway of EA signals transmitting to M1 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of the EA's effect is still in the exploration. Previous investigations have reported that neural activity in the primary motor cortex (M1) was enhanced by EA‐CV23 in PSD mice 8‐11 . When acupuncture is delivered to acupoints, the cortex is activated 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…[11] Combined with chemical genetics, electromyography recording, and immunofluorescence staining, it has been shown that electroacupuncture stimulation of acupoint lianquan can activate paraventricular hypothalamus neurons and regulate human swallowing function. [12] Thus, acupuncture can significantly improve the swallowing function of patients with swallowing disorder, with quick effects, few adverse reactions, convenient operation, low cost, and diversity of therapy. [13][14][15][16] During the epidemic of COVID-19, acupuncture has been used as a supplementary treatment of COVID-19 in China, and its curative effect has been proved by research.…”
Section: Introductionmentioning
confidence: 99%